Integrating culturally informed approaches into the physiotherapy assessment and treatment of chronic pain: protocol for a pilot randomised controlled trial. Issue 5 (12th May 2017) - Brady, Bernadette; Veljanova, Irena; Schabrun, Siobhan; Chipchase, Lucinda
Abstract : Introduction: There is strong evidence that biopsychosocial approaches are efficacious in the management of chronic pain. However, implementation of these approaches in clinical practice is known not to account for the beliefs and values of culturally and linguistically diverse (CALD) patients. This limitation in translation of research contributes to the disparities in outcomes for CALD patients with chronic pain adding to the socioeconomic burden of this prevalent condition. Cultural adaptation of chronic pain assessment and management is urgently required. Thus, the aim of this pilot randomised controlled trial (RCT) is to determine the feasibility, participant acceptance with and clinical effectiveness of a culturally adapted physiotherapy assessment and treatment approach when contrasted with 'usual evidence based physiotherapy care' for three CALD communities. Methods and analysis: Using a participant-blinded and assessor-blinded randomised controlled pilot design, patients with chronic pain who self-identify as Assyrian, Mandaean or Vietnamese will be randomised to either 'culturally adapted physiotherapy assessment and treatment' or 'evidence informed usual physiotherapy care'. We will recruit 16 participants from each ethnocultural community that will give a total of 24 participants in each treatment arm. Both groups will receive physiotherapy treatment for up to 10 sessions over 3 months. Outcomes including feasibility data, acceptance with the culturally adapted intervention, functional and pain-related measures will be collected at baseline and 3 months by a blinded assessor. Analysis will be descriptive for feasibility outcomes, while measures for clinical effectiveness will be explored using independent samples t-tests and repeated measures analysis of variance. This analysis will inform sample size estimates while also allowing for identification of revisions in the protocol or intervention prior to a larger scale RCT. Ethics and dissemination: This trial has full ethical approval (HREC/16/LPOOL/194). The results from this pilot RCT will be presented at scientific meetings and published in peer-reviewed journals. Trial registration number: ACTRN12616000857404